Posterior cortical atrophy: a single case cognitive and radiological follow-up. Issue 1 (2nd January 2018) - Esteves, Sol; Ramirez Romero, Diana Andrea; Torralva, Teresa; Martínez Cuitiño, Macarena; Herndon, Shannon; Couto, Blas; Ibañez, Agustín; Manes, Facundo; Roca, María
ABSTRACT: Posterior cortical atrophy (PCA) is a rare neurodegenerative syndrome characterized by initial predominant visuoperceptual deficits followed by a progressive decline in other cognitive functions. This syndrome has not been as thoroughly described as other dementias, particularly from a neuropsychological evolution perspective with only a few studies describing the evolution of its cognitive progression. In this investigation we review the literature on this rare condition and we perform a 7-year neuropsychological and neuroradiological follow-up of a 64-year-old man with PCA. The subject's deficits initially appeared in his visuoperceptual skills with later affectation appearing in language and other cognitive functions, this being coherent with the patient's parieto-temporal atrophy evolution.